IMPROVING THE QUALITY OF POWER IN YOUNG SAMBO WRESTLERS IN THE PROCESS OF DEALING WITH SAMBO WRESTLING - Ziyayev Abdurahmon Abdullayevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
the article examines the means and methods of applying complex programs of physical exercises in combination with heavy sports in improving the quality of strength in young sambo wrestlers in the process of dealing with sambo wrestling. The experimental experiment covered the results of samboists aged 17-19, divided into two groups.